Desempenho semântico, sintático, construção e extensão da frase em crianças com desenvolvimento fonológico típico e desviante - Albiero, Jamile Konzen (2012)
The aim in this research was to investigate a possible relation between the different subsystems of language, from children with disorders in the phonological subsystem and also to examine which mode of language enunciation seems to be more reliable in a way to better substantiate the concrete language ability of the children. The sample for this research was consisted of 71 children of both sexes, and of these total, 54 presented typical phonological development and 17 deviant. After making the phonological triage and the diagnosis of phonological disorder, the children were submitted to a language evaluation through the Average Value of the Phrase. In this evaluation, through three different modes of language enunciation the first five spoken phrases by children in each evaluated event are collected. Then, the sentences are scored according to their complexity, ie, different weights are assigned to syntactic elements and lexical elements of the sentence. After making the collection, the data are shown in tables according to age and the proposed variants. Later, these data were subjected to statistical analysis and, for comparison concerning all variables between the group with typical phonological development and the group with deviant phonological development and for making the comparison of the performance according to the age groups it was used the non-parametric Mann-Whitney U test. On the other hand, for the comparison between different severity degrees of phonological disorders for each kind of language it was used the technique of non-parametric Kruskal-Wallis test and for the comparison of performance between the modes of language enunciation in the group with typical phonological development and in the group with deviant phonological development, it was used the Test of Signals. In both tests, the significance level was set at 0.05 (p <0.05). As the results, it is possible to conclude that children with deviant phonological development do not show changes in semantic and syntactic subsystems of the language, despite the change in phonology, so they produce longer and well-developed sentences in order to facilitate their phonological production. It was also noted that the History mode of articulation of language shows the concrete language skills and grammar of the child, when compared to other evaluated modes, once the child produces narrative through sentences, using all her acquired knowledge during the development of the language.